Public Expenditure Management in Poland - Burns, Andrew (OECD Publishing, 2002)
This paper assesses the public expenditure system in Poland and the scope for its reform. Though a number of important steps to control the future evolution of spending, such as pension reform and healthcare reform, have already made in Poland, much more needs to be done. Indeed budget consolidation and the government's goal of increasing the economy's potential rate of growth can best be achieved by a far ranging re-evaluation and reorientation of spending away from personal transfers that contribute to inactivity traps. In this regard, it is important to expand the scope of the State Budget to include much more of general government spending, abolishing the extrabudgetary funds, and improving the co-ordination of the budget planning process among different levels of government. Moreover, the authorities need to increasingly move towards a multi-year budgeting framework. Not only will this allow for better management of investment projects, but it will also help policymakers to ...
Keywords: Economics; Poland